Lecture prof. dr. ir. C.L. Temminck Groll (Bulletin KNOB, 1989)
Why talking about Indonesia, Surinam and the Dutch Antilles on a congress clearly dedicated to Africa! This is meaningful, because the subject 'documentation, preservation and restoration of monuments' in the mentioned countries already is historic. Indonesia obtained its Ordinance of Monuments in 1931 (thus actual protection in Indonesia was possible sooner than in Holland itself!). With this the famous Hindu-Buddhistic Antiquities and the Dutch buildings from the East Indian Company-period could be protected The first already stood outside ordinary life for a long time. Next to the attraction of tourism their role was and is: strengthening the cultural identity of the country. With respect to the colonial buildings: here primarily a social function has been sought after. Since the late sixties the notion 'monument' in Indonesia underwent an important extension. In behalf of their study a working-group ARSI was founded. Since 1954 Curacao has a well functioning 'Foundation Protection of Monuments' with an increasing amount of properties. Here the direct social function - at present also the function of social housing - predominated that of tourist attraction, which indirectly of course is a matter of the utmost importance. Also on this field the island authorities see a task. Of the foundations on the other island notably the 'Historical Foundation' on St. Eustatius has to be mentioned, which on the contrary especially aims at the promotion of tourism. In Surinam during the sixties a lot of activity existed on this field. Generally these activities concerned socially functioning public buildings and museum projects. At the end of 1987 the interest revived and an Act of Monuments, already being prepared for a long time, finally had been accepted. Naturally financial problems in Surinam are extremely large and a problem, which is almost as large, is formed by the fast getting lost of good craftsmanship at restoration. Unfortunately this is also the case at the Antilles. Like in Indonesia old architecture and town-planning often are of such high quality, that their preservation not only serves the national interest, but also has to be considered as a matter of upper-national importance.